Health status of photovoltaic module production workers in Shanghai - Zhiping DUAN; Qinyu ZHANG; Xuetao ZHANG; Qiang HOU; Yulai TIAN; Jiming ZHANG; Zhijun ZHOU (环境与职业医学, 2024)
BackgroundPhotovoltaic (PV) cells can convert solar energy into electricity and alleviate the dilemma of energy supply shortage. Shanghai's PV module industry is booming, but there are few reports on the health status of the workers and there is an urgent need for health risk assessment. ObjectiveTo evaluate the health status of PV module production workers and the association between work and health status, in order to provide a direction for the health management of the workers. MethodsAmong the PV module production workers who completed prescriptive occupational health examination by a designated medical institution in 2021, 2453 workers with more than one year of working age were selected as the exposure group and 538 newly hired workers as the control group. On the basis of the Technical specifications for occupational health surveillance (GBZ 188−2014), the health examination included physical examination and laboratory examination and information such as sociodemographics, living habits, and disease history. We compared the indicators of pure-tone hearing test, blood routine examination, electrocardiogram (ECG), liver function, and kidney function between the two groups. The blood routine results included erythrocyte-related indicators, leukocyte-related indicators, and platelet-related indicators, and the results of liver function included hepatocyte injury indicators, hepatic secretory function indicators, and hepatic synthesis function indicators. The workers were divided into four groups by quartiles of working age. Trend chi-square test was used to analyze differences in health status between the four working age groups. Multiple logistic regression models were used to evaluate the association between working age and health indicators. ResultsAmong the exposure group workers, 2035 (83.0%) were male and 418 (17.0%) were female. The median (P25, P75) age was 34.0 (30.0, 39.0) years and the median (P25, P75) working age was 6.0 (3.0, 10.0) years. The abnormality rate of blood routine was 61.7%. Among them, the abnormality rates of platelet-related indicators and liver secretory function indicators were 39.8% and 48.1% respectively. The risks of abnormal hepatocyte injury-related indicators, fatty liver, and platelet-related indicator abnormalities among the exposure group were 1.471 (95%CI: 1.060, 2.054), 1.691 (95%CI: 1.208, 2.385), and 7.576 (95%CI: 4.967, 11.994) times higher than those in the control group respectively. The single-factor analysis demonstrated a positively linear trend between working age and hypertension prevalence, electrical audiometry abnormality rate, or liver secretory function indicator abnormality rate. Corrected for gender, age, smoking status, hypertension, etc., the results of logistic analysis showed that quartile working age was positively related to abnormal liver secretion function and abnormal platelet-related indicators respectively (OR=1.047, P=0.005; OR=1.037, P=0.014), and inversely associated with the abnormal rate of renal function (OR=0.953, P=0.044). ConclusionNegative associations between health status and working age are identified in PV module production workers. The target PV module production employees are in younger age, and with the increase of working age, the abnormalities of liver function and platelets may increase. Therefore, the enterprises should extend occupational health work from workplace to workers.